(untitled) (The Research of Medical Science Review, 2025)
Background: The goal of orthopedic surgery is to timely restore function to the affected area. The response of the surgery and immobility of the joint leads to increased activity of catabolic, nutritional issues, and loss of muscle mass, which is responsible for the recovery outcome. Many factors affect the health-related factors that impact the quality of life of a patient, such as the patient’s gender, age, type of surgery, duration of surgery, presence of other diseases, as well as pain control. Objective: To determine the perception of health-related factors and quality of life among post-operative adult orthopedic patients Methodology: The cross-sectional study was conducted from December 2024 to May 2025 in Karachi to determine the perception of health-related factors and quality of life among post-operative adult orthopedic patients. The sample size was 377, and the non-probability purposive sampling technique was used. Data was evaluated by two validated tools: the VAS scale and EQ-5D Health questionnaire. The data was analyzed through SPSS version 23.0. Result: A total of 377 orthopedic patients were included in this study. The response to the question related to mobility, 75.59% have some issues in walking, 45.88% said they have some issues in self-care, 51.72% had some issues in performing their ADLs, and 47.21% had some discomfort. The severity of pain was around 25.46%, had moderate pain as per the VAS scale. Conclusion: The Perception of orthopedic patients was extremely anxious, which affects their quality of life in performing ADLs.